The portable seminary - Horton, David (David E.) (Minneapolis, Minnesota Bethany House, 2006)
"Lay people and pastors will find the major topics included in this volume that would be found in a typical seminary master's program. The information is gleaned from a distinguished international faculty of more than fifty professors, lectures, and authors"----Provided by publisher
Keywords: Pastoral theology